2016
DOI: 10.1074/jbc.m115.693408
|View full text |Cite
|
Sign up to set email alerts
|

Fibromodulin Interacts with Collagen Cross-linking Sites and Activates Lysyl Oxidase

Abstract: The hallmark of fibrotic disorders is a highly cross-linked and dense collagen matrix, a property driven by the oxidative action of lysyl oxidase. Other fibrosis-associated proteins also contribute to the final collagen matrix properties, one of which is fibromodulin. Its interactions with collagen affect collagen cross-linking, packing, and fibril diameter. We investigated the possibility that a specific relationship exists between fibromodulin and lysyl oxidase, potentially imparting a specific collagen matr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
83
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(87 citation statements)
references
References 50 publications
(57 reference statements)
3
83
0
1
Order By: Relevance
“…It is possible that an inability to mature the collagen fibrils results from disturbances in the enzyme arrays responsible for cross-link formation. Recently, we showed that fibromodulin interacts with Lox and can direct collagen cross-link formation (45). A decreased expression of fibromodulin can result in an impairment of fibril maturation even if Lox is increased, as it was observed in the current study in which the expression of Lox and Loxl2 were increased.…”
Section: Discussionsupporting
confidence: 72%
“…It is possible that an inability to mature the collagen fibrils results from disturbances in the enzyme arrays responsible for cross-link formation. Recently, we showed that fibromodulin interacts with Lox and can direct collagen cross-link formation (45). A decreased expression of fibromodulin can result in an impairment of fibril maturation even if Lox is increased, as it was observed in the current study in which the expression of Lox and Loxl2 were increased.…”
Section: Discussionsupporting
confidence: 72%
“…Further studies suggested that fibromodulin interacts with lysyl oxidase supporting this conclusion (23). Interestingly, the shift in band intensity in the current mice was most prominent in skin, less so in tendon, and absent in bone collagen extracts.…”
Section: Generation Of P3h3supporting
confidence: 67%
“…Although this study did not analyze the contribution of residues C-terminal to the reactive lysine, found to be highly conserved in our work, these observations reflect a higher degree of complexity in the recognition of collagen chains by LOX than that brought about by short peptides in solution. To this respect, LOX enzymes have been shown to be more active with collagen forming fibrils than with solubilized forms as a substrate, and more importantly, their binding capacity highly influenced by collagen-binding proteins such as small leucine-rich proteins (SRLP)111241. Closely linked to this, LOX enzymes are also responsible for the cross-linking of tropoelastin monomers during the process of formation of elastic fibers, and sequence recognition within the tropoelastin chain very much differs from that observed in collagens42.…”
Section: Discussionmentioning
confidence: 99%
“…In fact, defects in PLOD2, the lysyl hydroxylase isoform that specifically acts on lysine residues in collagen telopeptides, are responsible for BrĂŒck syndrome, a heritable disorder in the osteogenesis imperfecta spectrum, characterized by severe reduction or elimination of the telopeptide hydroxylysine-derived cross-links, resulting in bone fragility10. In addition to lysyl hydroxylases, collagen-associated proteins such as the small leucine-rich protein (SLRP), fibromodulin, have been shown to influence collagen cross-linking, as recently evidenced in fibromodulin-deficient mice1112.…”
mentioning
confidence: 99%